Optimalisasi Pengadaan Jumlah Produksi Barang Mengggunakan Metode Fuzzy Mamdani - Badrul, Mohammad; Romadona, Ayu Asari Sofia (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The challenges in the industrial world faced by companies are increasingly competitive, both service companies, trade and manufacturing. In terms of operational management, one of them, companies must improve the effectiveness and efficiency of company operations through modern operational methods and models such as production planning, production management and improvement, and so on. PT. Surya Pelangi Nusantara Sejahtera is engaged in manufacturing plastic products with the brand name GreenLeaf. Warehouse or storage area of goods has undergone a full warehouse and resulted in the boxes as containers of goods so that the goods can be easily damaged and the quality of goods that cannot be maintained thus causing a large influence on the financial sector. That was caused by the result of production entering the warehouse was not balanced with the expenditure of goods, causing a full warehouse. to resolve the decision carried out using the Fuzzy Mamdani method. Optimization of the number of goods procurement is done by using three variables, namely sales, inventory and procurement. the result is that the Mamdani fuzzy method is accurate enough to determine the optimization of the amount of goods produced.